Hydrogen production from biomass by continuous fast pyrolysis and in-line steam reforming. Issue 31 (9th March 2016) - Arregi, A.; Lopez, G.; Amutio, M.; Barbarias, I.; Bilbao, J.; Olazar, M.
Abstract : The continuous fast pyrolysis of pine wood sawdust has been studied in a conical spouted bed reactor (CSBR) followed by in-line steam reforming of the pyrolysis vapours in a fluidised bed reactor on a Ni commercial catalyst. Abstract : The continuous fast pyrolysis (500 °C) of pine wood sawdust has been studied in a conical spouted bed reactor (CSBR) followed by in-line steam reforming of the pyrolysis vapours in a fluidised bed reactor on a Ni commercial catalyst. An analysis has been carried out on the effect reforming temperature in the 550–700 °C range, space time from 2.5 to 30 gcat min gvolatiles −1 and steam/biomass ratio between 2 and 5 have on the pyrolysis volatile conversion, H2 yield and gaseous stream composition. The continuous pyrolysis-reforming process has shown great potential for H2 production from biomass, with no operational problems and allowing for full conversion of pyrolysis vapours. Thus, a maximum H2 yield of 117 g per kg of biomass was obtained at 600 °C, at the highest space time studied (30 gcat min gvolatiles −1 ) and for a S/B ratio of 4. This yield is higher than those obtained by other alternatives, such as direct steam gasification or bio-oil reforming. Moreover, the char produced in the pyrolysis step has been continuously removed from the conical spouted bed reactor in order to be upgraded following promising valorisation alternatives.